Identification of Morphometric and Intensity of Marine Leech Zeylanicobdella Infestation on Cantang Grouper from Brondong District, Lamongan and Mandangin Island, Madura - Ririn Agustiya; Mahasri, Gunanti; Subekti, Sri (Universitas Airlangga, 2023)
Cantang grouper (Epinephelus fuscoguttatus lanceolatus) is the result of hybridization between female tiger grouper and male grouper fish which is widely cultivated because it has fast growth, easy to breed, and lower cannibalism. Cultivation of cantang grouper can be carried out in semi-intensive ponds and floating net cages (KJA) which have the potential for grouper nursery and rearing activities. One of the problems in the cultivation of cantang grouper is the presence of disease attacks caused by marine leeches Zeylanicobdella with a prevalence of up to 100% in grouper culture in floating net cages. This study aims to determine differences in species and intensity of marine leech Zeylanicobdella infestation in cantang grouper (Epinephelus fuscoguttatus lanceolatus) from semi-intensive ponds in Brondong District, Lamongan and floating net cages (FNC) on Mandangin Island, Madura. The method used in this research is a survey and sampling is done by purposive sampling method. Cantang groupers measuring 15-20 cm from semi-intensive ponds and 20-25 cm from floating net cages each were taken as many as 35 individuals. Identification of Zeylanicobdella marine leeches using a binocular microscope and making sketches of ectoparasites with the help of a binocular microscope equipped with a lucida camera. Marine leech species found to infest the cantang grouper (Epinephelus fuscoguttatus lanceolatus) is Zeylanicobdella arugamensis which was found on the body surface, fins, gills, and eyes. The results of statistical analysis using the Mann-Whitney U test showed that there was no significant difference (p>0,05) between species and intensity of Zeylanicobdella arugamensis in cantang grouper reared in semi-intensive ponds and floating net cages. The intensity of marine leeches Zeylanicobdella arugamensis in semi-intensive ponds was in the medium category (14,74 individuals/head) and in floating net cages was in the medium category (27,74 individuals/head). The highest intensity of infestation marine leeches Zeylanicobdella arugamensis in floating net cages of 27,74 individuals/head. There was no significant difference in the intensity of Zeylanicobdella arugamensis marine leech infestation in cantang grouper both from semi-intensive ponds and floating net cages (FNC) which were included in the medium category.